Investigation of the effects of viscous damping mechanisms on structural characteristics in coupled shear walls. (1st June 2016) - Moghadasi Faridani, Hadi; Capsoni, Antonio
Highlights: The effects of viscous damping mechanisms are investigated in coupled shear walls. Classical damping behaves similar to bending damping with small degrees of coupling. Bending damping is the efficient mechanism with every degree of coupling. Shear damping is the efficient mechanism with small degrees of coupling. Distributed shear damping is capable to model the passive damping. Abstract: This study addresses energy dissipation mechanisms to investigate the effects of the internal and external viscous damping on structural characteristics in coupled shear walls. A discrete Reference Beam (RB) is firstly proposed and a Distributed Internal Viscous Damping (DIVD), composed by bending and shear mechanisms, is defined. Meanwhile, the linear classical damping is considered. A low-order finite element method (FEM) is adopted for lateral analyses. For the sake of simplicity, a Generalized Sandwich Beam (GSB) is then developed through the replacement of the set of connecting beams of the RB by an equivalent elastic and dissipative core and a FEM is employed for its dynamic analysis. The passive damping modeling through the GSB is presented using continuous models. Concerning slender structures, the GSB is reduced to a Coupled Two-Beam (CTB) including the damping effects. The analytical solution of the CTB is presented to be a benchmark for the FE solutions. The validity of both numerical and analytical solutions is confirmed via numerical examples. The effectiveness of proposed damping models on dynamical responses and vibration characteristics are tested with respect to continuum-based controlling parameters, and a qualitative model is consequently proposed to appropriately choose the damping mechanisms depending upon the parameters of coupled shear walls. The suitability of various damping models is finally compared to current damping predictors and full-scale measured data given for RC buildings. The results reveal that the bending and shear damping are somehow efficient where the linear classical damping is incapable to be always a proper mechanism.